Supercritical Extraction of Flavonoid Compounds from Dorema aucheri Boiss. Experimental and Modeling Using CH2Cl2 as Co-Solvent - Kamyab Moghadas, B.; Safekordi, A.A.; Honarvar, B.; Fathi Kaljahi, J.; Vaziri Yazdi, S.A. (Asian Journal of Chemistry, 2012)
In recent years there is an increasing interest to replace chemically synthesized compounds by natural equivalents that can be found mostly in plant materials. Dorema aucheri Boiss. is a native Iranian plant, which has medicinal properties. In this work the extraction of flavonoid compounds from this plant, with supercritical carbon dioxide, is studied. A mathematical two phase model is developed to simulate extraction yield at different operating conditions (pressure, temperature, void bed fraction and dynamic extraction time). Results indicated that these parameters had significant effect on the extraction yield. After analyzing the extracted products by GC and GC/MS, a-eudesmol (39.2 %) and d-cadinene (12.9 %) were the major bioactive flavonoid compounds in this plant. The optimum pressure, temperature, void bed fraction and dynamic extraction time were 21 MPa , 318 K , 0.28 and 1 h, respectively. The present findings showed, supercritical extraction is a promising and alternative process for recovering the flavonoid compounds from Dorema aucheri with high concentration.